Research campaign: Macroscopic quantum resonators (MAQRO). (1st January 2023) - Kaltenbaek, Rainer; Arndt, Markus; Aspelmeyer, Markus; Barker, Peter F; Bassi, Angelo; Bateman, James; Belenchia, Alessio; Bergé, Joel; Braxmaier, Claus; Bose, Sougato; Christophe, Bruno; Cole, Garrett D; et al.
Abstract: The objective of the proposed macroscopic quantum resonators (MAQRO) mission is to harness space for achieving long free-fall times, extreme vacuum, nano-gravity, and cryogenic temperatures to test the foundations of physics in macroscopic quantum experiments at the interface with gravity. Developing the necessary technologies, achieving the required sensitivities and providing the necessary isolation of macroscopic quantum systems from their environment will lay the path for developing novel quantum sensors. Earlier studies showed that the proposal is feasible but that several critical challenges remain, and key technologies need to be developed. Recent scientific and technological developments since the original proposal of MAQRO promise the potential for achieving additional science objectives. The proposed research campaign aims to advance the state of the art and to perform the first macroscopic quantum experiments in space. Experiments on the ground, in micro-gravity, and in space will drive the proposed research campaign during the current decade to enable the implementation of MAQRO within the subsequent decade.